Multi-walled carbon nanotubes/graphene nanoribbons hybrid materials with superior electrochemical performance - Hernández Ferrer, Javier (2014)
Graphene nanoribbons (GNRs) were synthesized by oxidation of arc discharge multi-walled carbon nanotubes(MWCNTs) in concentrated H2SO4using KMnO4as oxidizing agent at different times from 15 to 120 min. Oneof the GNR samples was further electrochemically and chemically reduced. The material obtained after 15 minof oxidation time (GNR015) was a hybrid material containing MWCNTs, partially unzipped GNRs-MWCNTs andfully unzipped GNRs, and it demonstrated a superior electrochemical performance. This material presented thehighest heterogeneous charge transfer constant and sensitivity towards H2O2reduction. These properties aredue to the balance between the content of unzipped MWCNTs, Csp2carbon structure and oxygen moieties.GNR015, thus reveals as a promising platform for further applications in electrochemical sensing.